Training at Work : A Critical Analysis of Policy and Practice - Morin, Denis (Relations industrielles / Industrial Relations, 1993)
The article reviews the book, "Training at Work : A Critical Analysis of Policy and Practice," by Jeff Hyman.
Keywords: Book reviews; Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Employees; Labor Unions; SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z; Training